Low CD4 count may be a risk factor for non‐tuberculous mycobacteria infection in pediatric hematopoietic cell transplant recipients. (11th March 2021) - Wobma, Holly; Chang, Alicia K.; Jin, Zhezhen; Baker, Courtney; Garvin, James; George, Diane; Satwani, Prakash; Foca, Marc; Bhatia, Monica
Abstract: Background: HCT leaves patients in a relative state of immune deficiency both during their initial transplant admission and for several years following discharge. NTM are generally harmless colonizers of the outside environment, but for immunocompromised patients, they can cause significant disease due to a paucity of T‐cell defense. While routine prophylaxis against NTM is recommended for patients with low CD4 counts in certain clinical settings (eg, AIDS), this is not yet established for HCT patients despite their higher risk. Methods: Here we build upon our prior work to determine risk factors for NTM in pediatric HCT patients by comparing NTM patient characteristics to matched HCT controls. Results: We followed 272 patients across a 13‐year time period, with 11 cases of NTM. Patients with NTM had a significantly lower CD4 count at Day 365 than matched HCT controls (105.5 ± 97.0 cells/µl vs. 856.2 ± 446.1 cells/µl, respectively; p = .001). No other potential risk factors (eg, CMV, GvHD, disease type) were found to be statistically significant, including use of T‐cell depleting agents. This is consistent with an average diagnosis of NTM at Day +323 (ie, outside immediate post‐transplant period). All‐cause mortality was similar between NTM and control HCT groups, with an NTM attributable mortality of <10%. Conclusion: Since reduced CD4 counts are associated with NTM, and cost and morbidity are high, azithromycin prophylaxis for CD4 count <200 cells/µl in high‐risk patients should be considered.